Factors Affecting Permeability Reduction of MICP for Fractured Rock - Peng, Shuquan; Di, Hu; Fan, Ling; Fan, Wang; Qin, Liu (Frontiers in Earth Science, 2020)
Microbial induced Calcite Precipitation (MICP) has shown great potential to reduce the permeability of fractured rock, but its permeability reduction characteristic affected by solution concentration and the geometric morphology of fracture rock is not presented. Then MICP grouting and seepage test device were designed to study the effect of factors including urea and calcium chloride concentration, fracture roughness and aperture on permeability reduction of MICP on fracture rock. During the test, the same total volume was injected into each sample with the same injection times. The results showed that MICP grouting reduced the Darcy permeability coefficient of fractured rock to 3-5×10-5 m/s by 4 orders of magnitude smaller than that of non-grouted fractured rock. And with increasing of fracture roughness, the urea and calcium chloride concentrations and decreasing of fracture aperture, MICP grouting ratio in fractured rocks increased and the Darcy permeability coefficient decreased. And the permeability reduction of MICP on fracture rock increased with decreasing of the four factors. The permeability coefficient and the permeability reduction were the most sensitive to urea concentration. The permeability reduction could be fitted well by power function consider the above factors. The effects of fracture aperture larger than 2.5 mm or roughness larger than 0.873 mm need further research. The research results can provide important guidance and reference significance for microbial grouting to improve fractured rock performance.